Upaya Penurunan Risiko Perilaku Kekerasan Pada Dengan Melatih Asertif Secara Verbal - Habbi Yulsar Rahman, Fathul; , Arif Widodo, A.Kep., M.Kes (2017)
The background : Health is a point in human life and to get it requires more effort for example with regular exercise,always take care himself,environment,eat and drink nutritious. The human said to be healthy if the soul and physique is not impaired or injury resulting in health declined.The research health (RISKESDAS) the prevalence of severe mental disorders in Indonesia's population 1,7 per mile,and mental impaired emotional on Indonesia's populations of 6 percent.The disturbance of severe mental in Yogyakarta, Aceh,South Sulawesi, and Centre java. Proportion the home which had the members of the household severe mental disorders,3 percent and most in people who live in rural areas (18,2%),and at the group of the populations with kuintil the ownership of the lowest (19,5%). Behavior the violence is a state where a person who doing an act of violence,physical or verbal instructionthat it can harm yourself or others.Assertive training is a therapeutic modality the nurse in the form of therapy to behaviour,clients learn to express feelings of anger is appropriate or assertive as to be able to get in touch with other people, were able to declare : what you want, what you likes, what are you trying to do, and the ability to make a person feel uncomfortable talking about himself. Objectives :In order to reduce the risk of behavioral violence after a series of assertive verbally. Methods : The writer used descriptive methods with a case study for 3 x 24 hours Results : The client is able to know and can practice efforts the decrease the risk of behavioural violence after a series of assertive verbally. Conclusion : The client are able to build a trusting relationship to mention the cause ,a sign of symptoms due to what happens when angry,practice the techniques of breath in and hit the pillow. Client can also mention medicine are consumed and if don't drink it on a regular basis. Client also able to control anger by expressing,asked,refused to be a good,and control the angry with spiritual, client to routinely prayers five times, remembrance and pray.